Extended Pancreaticoduodenectomy for a Huge Cystic-Cavernous Lymphangioma: A Case Report - Erguney, Sabri; Teksoz, Serkan; Erdamar, Sibel; Ainechii, Sanaz; Olgun, Deniz Cebi (JOP. Journal of the Pancreas, 2012)
Context Cystic-cavernous lymphangioma is a rare cystic tumor especially for adults and pancreas. Case report We reported a case of a 33-year-old woman who presented with a visible and palpable abdominal mass found to be a huge lymphangioma of the pancreas. An abdominal magnetic resonance imaging (MRI) showed a multiloculated, lobulated T1 hypo/hyper, T2 hyperintense cystic mass extending from right subhepatic space to the pelvis measuring 155x167x100 mm. A pancreaticoduodenectomy was performed encompassing the distal stomach and a segment of the transverse colon, because of their close, inseparable relationship to the mass. The cystic mass was histopathologically diagnosed as partly cavernous and partly cystic lymphangioma. Conclusion To our knowledge this is the first case of pancreatic lymphangioma requiring additional organ resection besides a standard pancreaticoduodenectomy. To reduce recurrences, we recommend a complete resection for this pathology, even though its benign nature.